Design of a miniaturized planar half elliptical ultra‐wideband dipole using a concaved arm. Issue 10 (21st June 2019) - Guo, Lu; Min, Ming; Feng, Wenjie; Che, Wenquan; Yang, Wanchen
Abstract: This article presents the miniaturization of a planar half elliptical ultra‐wideband dipole. By simply placing a concaved arm in close proximity to the original structure, a 45% area reduction in terms of electrical wavelength can be achieved. The proposed antenna exhibits a wide measured return loss bandwidth of 2 to 9.9 GHz and omnidirectional radiation patterns across the band. The design features a footprint size of 41.5 × 41.5 mm 2 and an electrical size of 0.28 λ  × 0.28 λ at 2 GHz. Compared with some previously reported planar designs, the proposed antenna presents a more compact electrical dimension and better or comparable bandwidth. Critical geometric parameters of the structure, particularly the concaved arm, are investigated to understand the miniaturization and operating mechanism of the design. Satisfactory correlation between the simulation and measurement data is obtained.